Exploring Mosques in Selangor: Their Role as Hubs for Local Economic Activities - Mahmad Robbi, Ahmad Akram; Md. Sawari, Mohd Fuad; Abdullah , Muhammad Mui’izz; Alias, Muhammad Nazir; Mohd Dasar, Mohd Hafiz (International Journal of Economics, Management and Accounting, 2026)
Historically, mosques can function as centers for community economic development, drawing from their historical role dating back to Prophet Muhammad’s (sal-Allahu 'alayhi wa sallam) era. The study specifically investigates how mosques in Selangor are contributing to community sustainability through various microeconomic initiatives. By employing a qualitative study, the derivation of the primary data is based on in-depth interview and open-ended questions to obtain information regarding the execution of the mosque economic activities. The interview sessions were conducted with the mosques’ management within Selangor district. In addition, the secondary data were based on the library research which consist of analyzing books, journals, fatwas, websites as well as newspapers related to the contribution of mosques in facilitating social economy. The result indicates that the execution of the microeconomic-based mosque has impacted positive social economic activity among people who live in Selangor area. This turns the opportunities for the local people to get involved in small and medium entrepreneurship and reducing unemployment there. Also, the idea of developing the mosque as one stop center for the society to perform economic activities was highly recommended by the authorities. This finding demonstrates how mosques in Selangor can be effectively transformed into vital centers for community economic development. This study has the potential to be the pioneer in addressing the necessity of enlarging the role of the mosques as a centre of microeconomic development.